Kecerdasan Emosional dan Kecerdasan Spiritual Meningkatkan Kompetensi Sosial Guru - Puluhulawa, Citro W.. (UI Scholars Hub, 2013)
Teacher as a professional educational is demanded to have a set of competence in carrying out the daily tasks. One of the competences is social competence. The social competence of teachers is that teachers have an objective, inclusive and non discriminative attitude, well-mannered eitherin speech or in act, capable in communicating verbally, writtenly and gesture. In addition, teachers have to coordinate with the students, other fellow teachers, educational staff, student’s parents as well asthe society. They must also be able to adapt with the community. This study aims to determine the relationship between emotional intelligence and spiritual intelligence work with the social competence of teachers in Vocational Schools of Gorontalo City. The result of multiple correlation coefficient which showed between emotional intelligence and spiritual intelegence toward social competence. This means that the better the emotional and spiritual intelligence of teacher, the better the effect of the social competence of teachers will be.